Human Umbilical Cord Mesenchymal Stem Cells Encapsulated with Pluronic F-127 Enhance the Regeneration and Angiogenesis of Thin Endometrium in Rat via Local IL-1β Stimulation. (18th June 2022) - Zhou, Shuling; Lei, Yu; Wang, Ping; Chen, Jianying; Zeng, Liting; Qu, Ting; Maldonado, Martin; Huang, Jihua; Han, Tingting; Wen, Zina; Tian, Erpo; Meng, Xiangqian; et al.
Abstract : Thin endometrium (< 7 mm) could cause low clinical pregnancy, reduced live birth, increased spontaneous abortion, and decreased birth weight. However, the treatments for thin endometrium have not been well developed. In this study, we aim to determine the role of Pluronic F-127 (PF-127) encapsulation of human umbilical cord mesenchymal stem cells (hUC-MSCs) in the regeneration of thin endometrium and its underlying mechanism. Thin endometrium rat model was created by infusion of 95% ethanol. Thin endometrium modeled rat uterus were treated with saline, hUC-MSCs, PF-127, or hUC-MSCs plus PF-127 separately. Regenerated rat uterus was measured for gene expression levels of angiogenesis factors and histological morphology. Angiogenesis capacity of interleukin-1 beta (IL-1 β )-primed hUC-MSCs was monitored via quantitative polymerase chain reaction (q-PCR), Luminex assay, and tube formation assay. Decreased endometrium thickness and gland number and increased inflammatory factor IL-1 β were achieved in the thin endometrium rat model. Embedding of hUC-MSCs with PF-127 could prolong the hUC-MSCs retaining, which could further enhance endometrium thickness and gland number in the thin endometrium rat model via increasing angiogenesis capacity. Conditional medium derived from IL-1 β -primed hUC-MSCs increased the concentration of angiogenesis factors (basic fibroblast growth factor (bFGF), vascular endothelial growth factors (VEGF), and hepatocyte growth factor (HGF)). Improvement in the thickness, number of glands, and newly generated blood vessels could be achieved by uterus endometrium treatment with PF-127 and hUC-MSCs transplantation. Local IL-1 β stimulation-primed hUC-MSCs promoted the release of angiogenesis factors and may play a vital role on thin endometrium regeneration.